PSIKOEDUKASI SMART PARENTING TENTANG KARAKTERISTIK ANAK BERKEBUTUHAN KHUSUS (ABK) - Pamela Hendra Heng (MADANI: Jurnal Pengabdian Kepada Masyarakat, 2021)
Children with special needs (ABK) are very different from normal children in terms of needs, health, education, teaching, how to give advice and attention. Children with special needs require special treatment because they have developmental disorders and others disorders from children in general (Desiningrum, 2016). In 2015, Indonesia had approximately 4.2 million ABK. Baska and Stambaugh (in Juwono and Kumara, 2011) state that education services in Indonesia are still experiencing difficulties due to the lack of knowledge of teachers about ABK. Sunardi, Yusuf, Gunarhadi, Priyono, and Yeager (2011) state that in Indonesia, almost no changes have been made to accommodate the education program for children with special needs in inclusive schools; there is no difference in teaching strategies for children with special needs (Kurniawati, De Boer, Minnaert, and Mangunsong, 2017; Mangungsong 2014). The Holland Interests Test, the written Learning Style test and the Multiple Intelligence seminar were attended by 42 adolescents, analyzed by psychologists to determine their interests and talents. A psychoeducation approach through the smart parenting seminar "Mengasuh kidz jaman now" attended by 101 parents, teachers and church practitioners, aimed to give an understanding of the characteristics of children with special needs at church X in East Java.